Treatment of fabry disease: Current and emerging strategies - Rozenfeld, Paula Adriana (2011)
Fabry disease is an X-linked lysosomal storage disorder (LSD) due to deficiency of the enzyme α-galactosidase A (GLA). Absent or reduced enzyme activity leads to impaired catabolism of neutral glycosphingolipids, particularly globotriaosylceramide (Gb3), resulting in intracellular deposition of such lipids. Clinical manifestations in hemizygote males include angiokeratoma, hypohydrosis, acroparesthesia, abdominal pain, proteinuria, renal insufficiency, left ventricular hypertrophy and cerebrovascular accidents. Heterozygote women may present with mild to severe signs and symptoms. Since year 2001, enzyme replacement therapy (ERT) is the only specific treatment for Fabry disease. The beneficial effect of ERT on different organs/systems has been extensively evaluated, and an improvement in renal function, cardiac mass and quality of life has been reported. Different treatment approaches are currently on development. One of them implies the use of the active-site-specific chaperone 1-deoxygalactonojirimycin that acts facilitating folding of mutant GLA in the endoplasmic reticulum and increasing its lysosomal residual activity. Reduction of Gb3 deposits has been shown in lymphoblasts from Fabry patients with missense mutations and transgenic mouse model expressing a missense mutation GLA. Gene therapy has been also developed as a potential option for treatment of Fabry disease. This review will discuss these novel therapeutic options along with their advantages and limitations.